Noise Levels and Use of Ear Protectors in Hydraulic and Manual Steel Pressing Labor at CV. Medan City Sumatra Steel in 2022 - Rahmat, Adi; Nasution, Sri Bulan (International Archives of Medical Sciences and Public Health, 2023)
With the growth of the industry, it is increasingly encouraging the emergence of environmental problems, namely the increasing level of exposure to noise (TWA - Time Weighted Average) both in the work environment and in the surrounding environment, especially from the sound of production machines which can cause hearing loss and communication work accidents caused by two groups, namely , human actions that do not meet the requirements of a healthy life and unsafe environmental conditions. 80-85% of work accidents are caused by negligence or human error. Existing human factors generally affect PPE on the grounds that the use of PPE is considered to interfere with work and has a less protective effect. Continuous noise is noise that occurs continuously and is not interrupted. In the CV Baja Sumatra industry, pressing activities are often carried out and emit continuous noise. The aim is to describe the use of ear protection devices in the workforce and measure noise levels in the steel pressing section as well as review the impact on workers, and seek information about worker health benefits. As input for workers about the importance of wearing ear protection and the dangers of noise.